Effect of sucrose and kinetin on the quality and vase life of Bougainvillea glabra var. Elizabeth angus bracts at different temperature - Moneruzzaman, K.M.; Boyce, A.N.; Abms, H.; Saifudin, M.; Imdadul, H.; Wirakarnain, S. (2010)
A study was conducted to investigate the effects of sucrose and kinetin on the post harvest quality and vase life of Bougainvillea bracts at different storage temperature. Bougainvillea bracts and flower (Bougainvillea glabra) of the same age and size were used in the experiments. Fresh bracts were continuously treated with 200 mg/l sucrose, 200mg/l kinetin and control (water) at 10 degrees C, 20 degrees C and 28 +/- 1 degrees C. It was observed that sucrose treated bracts exhibited the longest vase life compared to the control and kinetin treatments at different temperatures. The higher temperature has promoted water uptake, senescence, and abscission. All the treatments showed a shorter vase life at a higher temperature. Kinetin treated flowers exhibited a shorter vase life than the control at all the temperature. The vase life was the longest in sucrose at a low temperature (10 degrees C). Weight loss and water uptake initially increased up to the 3(rd) day of storage irrespective of the different treatments but subsequently decreased linearly. The results showed that sucrose and lower temperature were the most effective factors in extending the vase life as well as quality of bougainvillea bracts.